Effective leaf rust resistance genes of wheat in Novosibirsk Province in connection with the variability of the Puccinia triticina population - L. P. Sochalova; N. I. Boyko; A. A. Poteshkina; V. V. Piskarev (Труды по прикладной ботанике, генетике и селекции, 2023)
Background. Information on the races of Puccinia triticina Erikss. in Novosibirsk Province is needed to identify sources of effective genes for leaf rust resistance. The goal hereof was monitoring genetic variability of the P. triticina population in the Ob riverside forest-steppe, Novosibirsk Province, and detecting effective resistance genes to develop wheat cultivars resistant to the disease.   Materials and methods. In 2015–2019, affliction of Thatcher lines (Tc) and cultivars under the disease pressure was assessed, and P. triticina structure in the Ob forest-steppe of Novosibirsk Province was monitored. P. triticina genotypes were identified using the Long–Kolmer system. Additionally, a set of cultivars with the Lr19, Lr20, Lr28, Lr39; 6 – Lr6Agi2, Lr6Agi1, LrKu, and LrSp2 genes was employed.   Results. A high frequency of virulence was detected for cultivars with the Lr3ka, Lr10, Lr1, Lr2a, Lr2c, Lr3a, Lr11, Lr18, Lr20, Lr30, Lr16, Lr17, and LrB genes (66.7–100 %). The P. triticina structure consisted of 27 races, including 12 common ones: TGTT GB, TGTR GB, TQTT GB, TQTR GB, TGPT GB, THFR GB, KHTT GB, PHKT GB, PQTT GB, THTP BB, PGFR GB, and SGPR GB. Genotypes with the Lr6Agi2, Lr6Agi1, LrKu, Lr39, Lr42, Lr12, Lr19, Lr24, Lr25, Lr28, Lr35, Lr45, Lr47, Lr50, Lr52, LrSp2, Lr6Agi1+Lr19, Lr6Agi2+Lr10+Lr34, Lr11+Lr13+Lr22a, Lr13+LrTb, Lr24+Lr26, Lr37+Lr13, Lr37+Lr1, Lr34+Lr13, Lr43+Lr24, and Lr49+Lr34 genes were resistant to P. triticina under the infection pressure. Some wheat genotypes varied in leaf rust resistance across the years (0–5 % for TcLr29 and TcLr21, 0–10 % for CSP 44 and TcLr44, 0–20 % for TcLr13, 1–30 % for TcLr37, and 15–80 % for Pavon F 76).   Conclusion. The local leaf rust population has changed slightly over the years of study (the Lr18 and Lr38 genes have lost resistance), and was very different from the population before 2010.